An innovative rehabilitation program for the veterans affairs post‐acute skilled nursing setting: Preliminary results. Issue 4 (13th January 2023) - Ashcroft, Taarika; Middleton, Addie; Driver, Jane A.; Ruopp, Marcus; Harris, Rebekah; Bean, Jonathan F.
Abstract: Background: Skilled nursing rehabilitative care plays a critical role in older adults' functional recovery impacting post‐discharge outcomes. Variations across post‐acute rehabilitative care services and patient outcomes indicate a need to improve rehabilitative care in this setting. We adapted a successful outpatient care program (Live Long Walk Strong‐LLWS) to address this need in post‐acute care settings within the Veterans Health Administration. LLWS differs from standard PT care by treating impairments linked to functional decline that are not traditionally targeted by standard care, providing formalized coaching to optimize behavior change, and providing post‐discharge case management to optimize long‐term outcomes. The purpose was to adapt, refine and implement the LLWS program for the Community Living Center (CLC), determine its acceptability and feasibility, and evaluate its preliminary effectiveness among older adults. Methods: The design of the program was adapted from the original outpatient LLWS program to the CLC setting through quality improvement methods and the Replicating Effective Programs (REP) framework. Primary outcomes included measures of feasibility and acceptability of >80% enrollment and completion of sessions as well as preliminary effectiveness using performance‐based and patient‐reported measures of function including the Short Physical Performance Battery (SPPB), AM‐PAC, a Global Rating of Change questionnaire, and a satisfaction survey. Results: After 18 months, 51 Veterans had enrolled in the LLWS program, with 94.1% maintaining enrollment. We observed >80% completion of the inpatient and home follow‐up sessions. Most patients were highly satisfied with care. Improvements in the SPPB (2.3 (SD 2.2) points), gait speed (0.17 (0.14) m/s) and the AM‐PAC (6.5 (SD 5.7)) surpassed clinically meaningful thresholds. Conclusions: This novel care program is feasible and acceptable to Veterans, demonstrating preliminary effectiveness with improving functional outcomes. Future research is needed to further examine the program's impact on other important outcomes relative to standard modes of care.